2014
DOI: 10.1016/j.atmosenv.2014.05.073
|View full text |Cite
|
Sign up to set email alerts
|

Current ozone levels threaten gross primary production and yield of Mediterranean annual pastures and nitrogen modulates the response

Abstract: Pastures are among the most important ecosystems in Europe considering their biodiversity and distribution area. However, their response to increasing tropospheric ozone (O3) and nitrogen (N) deposition, two of the main drivers of global change, is still uncertain. A new Open-Top Chamber (OTC) experiment was performed in central Spain, aiming to study annual pasture response to O3 and N in close to natural growing conditions. A mixture of six species of three representative families was sowed in the field. Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 31 publications
3
22
0
Order By: Relevance
“…This is primarily through a decrease in the size of the soil carbon pool as a result of reduced litter input to the soil, consistent with reduced GPP and NPP. Field studies show that in some regions of Europe, soil carbon stocks are decreasing (Bellamy et al, 2005;Capriel, 2013;Heikkinen et al, 2013;Sleutel et al, 2003). The study of Bellamy et al (2005), for example, showed that carbon was lost from soils across England and Wales between 1978 and 2003 at a mean rate of 0.6 % per year with little effect of land use on the rate of carbon loss, suggesting a possible link to climate change.…”
Section: Impacts Of O 3 At the Land Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…This is primarily through a decrease in the size of the soil carbon pool as a result of reduced litter input to the soil, consistent with reduced GPP and NPP. Field studies show that in some regions of Europe, soil carbon stocks are decreasing (Bellamy et al, 2005;Capriel, 2013;Heikkinen et al, 2013;Sleutel et al, 2003). The study of Bellamy et al (2005), for example, showed that carbon was lost from soils across England and Wales between 1978 and 2003 at a mean rate of 0.6 % per year with little effect of land use on the rate of carbon loss, suggesting a possible link to climate change.…”
Section: Impacts Of O 3 At the Land Surfacementioning
confidence: 99%
“…In recent decades much attention has focussed on the effects of rising atmospheric CO 2 on vegetation productivity (Ceulemans and Mousseau, 1994;Norby et al, 1999Norby et al, , 2005Saxe et al, 1998). The Norby et al (2005) synthesis of FreeAir CO 2 Enrichment (FACE) experiments suggests a median stimulation (23 ± 2 %) of forest net primary production (NPP) in response to a doubling of CO 2 .…”
mentioning
confidence: 99%
“…In a monitoring study of undisturbed headwater catchments in N Spain, it has been described a deposition-driven increase of N exportation from perennial grasslands to aquatic ecosystems (Camarero and Aniz, 2010). (Sanz et al , 2015Calvete-Sogo et al, 2014). Fertilization experiments in mountain heathlands of the Cantabrian Range have described an increase in the abundance of arthropod herbivores in the short-term (Cuesta et al, 2008) and a significant increase in total plant richness in the long term, due to an increase in the number of perennial herbs without displacing the dominant woody species (Calvo et al,.…”
Section: Effects Of Deposition Of Atmospheric N R In Spanish Terrestrmentioning
confidence: 99%
“…However, recent publications suggest that the addition and interaction of different stress factors (O 3 , N deposition, drought) can be affecting the growth of the trees Gerosa et al, 2015) and accompanying pastures (Calvete-Sogo et al, 2014. Thus, monitoring of nitrogen compounds such as NH 3 and HNO 3 should be incorporated into air quality monitoring networks (in most of them NO 2 and O 3 are already monitored).…”
Section: Assessment Of the Threats Caused By N Gaseous Pollutantsmentioning
confidence: 99%
See 1 more Smart Citation